Tindakan Represif Aparat Penegak Hukum dalam Aksi Unjuk Rasa terhadap Kebijakan Pemerintahan Prabowo dalam Perspektif Hak Asasi Manusia - Ninin Armianti Natsir; Santy Isma Handikasari; Nurul Fajriani; Ryan Asprimagama; Surez Taruna Pramata; Insan Tajali Nur (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Our country is known as a nation that upholds human rights values. This is manifested in the recognition of the right to express opinions, which is specifically regulated in Law Number 9 of 1998 concerning Freedom of Expression in Public. Along with the increasing dynamics of political contestation and polarization in society, the frequency of demonstrations has also escalated. This condition places the professionalism and neutrality of the police force under increasing public scrutiny. The reduction in citizens' freedom to express their aspirations often creates a negative image of the police, particularly due to repressive actions and the use of discretion that is deemed disproportionate. Based on a normative juridical approach, this study aims to analyze the extent to which the state upholds access and protection of freedom of expression in public, as well as examine the application of human rights principles from both national and international legal perspectives in demonstrations